2022
DOI: 10.3390/v14020207
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Responses after SARS-CoV-2 Vaccination in Patients with Liver Diseases

Abstract: The novel mRNA-based vaccines against SARS-CoV-2 display encouraging safety and efficacy profiles. However, there is a paucity of data regarding their immunogenicity and safety in patients with liver diseases (PWLD), especially in those with cirrhosis. We prospectively assessed anti-SARS-CoV-2 S-spike IgG antibodies and neutralizing activity in fully vaccinated PWLD (n = 87) and controls (n = 40). Seroconversion rates were 97.4% (37/38) in cirrhotic PWLD, 87.8% (43/49) in non-cirrhotic PWLD and 100% (40/40) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 41 publications
(49 reference statements)
4
39
0
2
Order By: Relevance
“…Most of the published data on seroconversion rates in cirrhosis following COVID-19 vaccination are with mRNA vaccines (BNT162b2; BioNTech SE/Pfizer or mRNA-1273; Moderna Biotech) or whole-virion-inactivated vaccines (CoronaVac, BBIBP-CorV, or WIBP-CorV) and seroconversion rates following ChAdOx1-nCOV vaccine are relatively unexplored [ 24 – 30 ]. The seroconversion rate of 92.1% observed in our cohort of patients with cirrhosis is similar to the impressive seroconversion rate of 96–100% reported by various studies using two doses of mRNA vaccines in cirrhosis [ 24 28 ]. However, the seroconversion rate of 66.1–78.9% with whole-virion-inactivated vaccines (CoronaVac, BBIBP-CorV, or WIBP-CorV) reported in two multicentric studies from China appear to be substantially lower than what was observed by us with ChAdOx1-nCOV or has been previously reported with mRNA vaccines [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Most of the published data on seroconversion rates in cirrhosis following COVID-19 vaccination are with mRNA vaccines (BNT162b2; BioNTech SE/Pfizer or mRNA-1273; Moderna Biotech) or whole-virion-inactivated vaccines (CoronaVac, BBIBP-CorV, or WIBP-CorV) and seroconversion rates following ChAdOx1-nCOV vaccine are relatively unexplored [ 24 – 30 ]. The seroconversion rate of 92.1% observed in our cohort of patients with cirrhosis is similar to the impressive seroconversion rate of 96–100% reported by various studies using two doses of mRNA vaccines in cirrhosis [ 24 28 ]. However, the seroconversion rate of 66.1–78.9% with whole-virion-inactivated vaccines (CoronaVac, BBIBP-CorV, or WIBP-CorV) reported in two multicentric studies from China appear to be substantially lower than what was observed by us with ChAdOx1-nCOV or has been previously reported with mRNA vaccines [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 89%
“…Further, Thuluvath et al reported suboptimal antibody responses in 19% patients with optimal antibody levels in 77.2% of 79 patients with cirrhosis [ 24 ]. On the contrary, a study from Greece reported adequate neutralizing activity in 92.1% of the 38 patients with cirrhosis following two doses of mRNA vaccines [ 28 ]. In our study, undetectable and low antibody responses were seen in 7 (7.9%) and 6 (6.8%) patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine immunogenicity Patients with CLD have been shown to have anti-SARS-CoV-2 S-spike IgG seroconversion rates of >85% following two vaccine doses [281]. However several studies have suggested that patients with cirrhosis may have a more rapid decline in antibody titers over time compared to healthy controls [281,282]. In contrast, LT recipients remain at high-risk for suboptimal humoral responses to vaccination.…”
Section: Vaccine Responsiveness In Patients With Cld and In Liver Tra...mentioning
confidence: 99%
“…The serological findings are coherent with those reported by Thuluvath et al [ 10 ] to support diminished humoral responses after COVID-19 vaccination in cirrhotic patients. However, this difference in antibody responses was less pronounced after the second vaccine dose, which may account for the lack of significance noted in some studies [ 11 , 18 ].…”
Section: Discussionmentioning
confidence: 95%